Implementasi Proyek Penguatan Profil Pelajar Pancasila dalam Mengembangkan Karakter Peserta Didik - Bertari, Tri Adhi; Abdullah, Ghufron (PGRI Kota Semarang, 2024)
Character education is a continuous and never-ending process. Character education emphasizes example, creating an environment, and habituation through various scientific tasks and activities. The aim of this research is to find out how management strengthens and develops character education at SMA Negeri 1 Subah, Batang Regency. The implementation of the project to strengthen the profile of Pancasila students in developing the character of SMA Negeri 1 Subah students is closely related to school management. Management of strengthening and developing students' character education includes: (1) Planning stage for strengthening and developing character education; (2) Stage of organizing the strengthening and development of character education; (3) Implementation stage of strengthening and developing character education; (4) and Supervision stage of strengthening and developing character education.This research uses a qualitative approach. Data collection techniques use observation, interviews and documentation. The data collected from this technique was analyzed using data reduction, data presentation, and verification through several informants, namely: the principal, head of curriculum, head of student affairs, P5 facilitator coordinator and class X students. Meanwhile, to test the validity of the data through a credibility test using using observation and grouping data from various sources, transferability, triangulation (sources and techniques), certainty and discussion. Based on the results of the research and discussion, it can be concluded that the strengthening and development of character education at SMA Negeri 1 Subah is carried out in four main activities, namely: learning activities, Pancasila Student Profile Strengthening Project activities (P5), extracurricular activities, habituation activities with the results stating that students can Carry out your role as a good citizen by continuing to play an active role in strengthening and developing character which is realized by familiarizing yourself with all aspects of activities at school and to increase competence in the role of teacher and coach, competency training is needed in stages.